Polymer composite gel for heavy metal ion adsorption and preparation method and application thereof

DE/CS-PEI@SA, diatomaceous earth, chitosan, polyethyleneimine and sodium alginate composite gel material prepared by ion cross-linking solves the problems of cumbersome preparation process and low adsorption performance in the existing adsorbents, and achieves efficient adsorption of heavy metal ions and has the characteristics of recycling.

CN119657092APending Publication Date: 2025-03-21ANHUI POLYTECHNIC UNIV

Patent Information

Application Number
CN202411760921.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The preparation process of existing heavy metal ion adsorbents is cumbersome and has low adsorption performance, making it difficult to meet the needs of industrial applications.

Method used

The composite gel material DE/CS-PEI@SA was prepared by ion cross-linking method using diatomaceous earth, chitosan, polyethyleneimine and sodium alginate as raw materials, with uniform morphology and good thermodynamic stability.

Benefits of technology

When this composite gel material adsorbs heavy metal ions Pb(II) and Cu(II), the maximum adsorption amount can reach 295.04 and 174.39 mg/g, respectively, showing high-efficiency ion adsorption performance and can be recycled and reused.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119657092A_ABST
    Figure CN119657092A_ABST
Patent Text Reader

Abstract

The invention provides a polymer composite gel for heavy metal ion adsorption and a preparation method and application thereof, diatomite DE, chitosan CS, polyethyleneimine PEI and sodium alginate SA are used as raw materials, and polymer modification crosslinking is promoted through an ionic crosslinking method to form the composite gel. Compared with the prior art, SA is a biodegradable natural polysaccharide material, contains rich hydroxyl and carboxyl functional groups and is used as a controllable modification site, DE is used as an inorganic clay material, has a layered porous structure and contains rich active sites, and CS and PEI polymer surfaces have rich amino and hydroxyl groups and are used as ion adsorption sites. Meanwhile, PEI is used as a nucleation site and an ionic cross-linking agent to promote material modification and cross-linking to form composite gel. The composite gel is used as an ion adsorbent, can be adsorbed through chemical chelation between functional groups and ions, and can also be physically adsorbed through a porous structure, so that the composite gel shows efficient ion adsorption performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of functional materials, and in particular relates to a polymer composite gel for heavy metal ion adsorption and a preparation method and application thereof. Background Art

[0003] At present, among various heavy metal ion removal technologies including chemical precipitation, ion exchange, adsorption and membrane separation, adsorption has become the most widely studied and applied process because of its advantages such as low energy consumption, high economic feasibility, simple operation process, mild conditions, no secondary pollution and high technical efficiency.

[0004] The key to whether the adsorbent method can effectively adsorb heavy metal ions lies in the selection and construction of the adsorbent. At present, researchers mainly improve the adsorption effect by preparing adsorbents with high specific surface area, high porosity and more functional group active adsorption sites. Commonly used high-porosity adsorbents include activated carbon, activated alumina and silica gel.

[0005] The Chinese patent with publication number CN 111482163 A published on August 4, 2020, discloses a method for preparing an enhanced chitosan-based aerogel for adsorbing heavy metal ions, which uses sol-gel and freeze-drying technology and a post-chemical modification method to prepare an enhanced chitosan-based aerogel adsorption material. However, the preparation process requires repeated freezing and thawing, which is cumbersome.

[0006] Therefore, it is very necessary to provide an adsorbent with a simple preparation method and high adsorption performance. Summary of the invention

[0007] The object of the present invention is to provide a polymer composite gel for heavy metal ion adsorption and a preparation method thereof. Diatomaceous earth (DE), chitosan (CS), polyethyleneimine (PEI) and sodium alginate (SA) are selected as raw materials, and a composite gel material DE / CS-PEI@SA is prepared by an ion crosslinking method. The composite gel material DE / CS-PEI@SA has a uniform morphology and good thermodynamic stability, can be recycled and reused after adsorption, and the preparation method of the present invention is simple and does not require repeated freezing and thawing.

[0008] Another object of the present invention is to provide an application of a polymer composite gel for heavy metal ion adsorption, which is used for heavy metal ion adsorption, especially for the adsorption of heavy metal ions Pb (II) and Cu (II), and the maximum adsorption amount can reach 295.04 and 174.39 mg / g respectively. As an ion adsorbent, the composite gel can be adsorbed by chemical chelation between functional groups and ions, and can also be adsorbed by physical adsorption through porous structures, thus showing high efficiency of ion adsorption performance.

[0009] The specific technical solutions of the present invention are as follows:

[0010] A method for preparing a polymer composite gel for heavy metal ion adsorption comprises the following steps:

[0011] 1) After ultrasonically dispersing diatomite DE and sodium carbonate in water, a saturated calcium chloride solution is added until precipitation is complete to obtain CaCO3 / DE; CaCO3 / DE is mixed with chitosan CS in a buffer solution, and stirred for reaction to obtain chitosan-modified diatomite DE / CS;

[0012] 2) Chitosan-modified diatomaceous earth DE / CS and polyethyleneimine PEI are added to a sodium alginate SA aqueous solution, and after ultrasonic dispersion, the mixture is heated for reaction. The obtained mixed solution is then dropped into a calcium chloride solution. After the cross-linking reaction, the mixture is soaked in hydrochloric acid, washed, and freeze-dried to obtain a DE / CS-PEI@SA composite gel.

[0013] In step 1), the mass ratio of diatomaceous earth to sodium carbonate is 1:0.5-0.6; the dosage ratio of diatomaceous earth to water is 1:20;

[0014] In step 1), CaCO3 / DE and chitosan are mixed in a buffer solution, wherein the mass concentration of chitosan is 0.4%; the mass concentration of CaCO3 / DE is 2%;

[0015] In step 1), the buffer solution is a Tris-HCl buffer solution with a concentration of 10 mmol and a pH of 8.5.

[0016] In step 1), the stirring reaction refers to stirring the reaction at room temperature for 10 hours;

[0017] In step 1), after stirring for reaction, washing and drying are performed to obtain chitosan-modified diatomaceous earth DE / CS;

[0018] In step 2), the mass ratio of chitosan-modified diatomaceous earth DE / CS to sodium alginate in the sodium alginate aqueous solution is 1:0.5-3;

[0019] In step 2), the mass ratio of chitosan-modified diatomaceous earth DE / CS to polyethyleneimine PEI is 1:0.5-2;

[0020] In step 2), the mass concentration of sodium alginate in the sodium alginate aqueous solution is 1%;

[0021] In step 2), the heating reaction refers to the reaction at 60° C. for 6 hours;

[0022] In step 2), the cross-linking reaction is carried out at room temperature for 12 hours;

[0023] In step 2), the volume ratio of the mixed solution to the calcium chloride solution is 1-1.5:1;

[0024] In step 2), the concentration of the calcium chloride solution is 3% (w / v, w in g, v in mL);

[0025] In step 2), the hydrochloric acid soaking has a concentration of 0.1 M;

[0026] In step 2), the washing refers to washing with sodium hydroxide solution and water, and the concentration of the sodium hydroxide solution used is 0.1M;

[0027] In step 2), the freeze drying refers to freeze drying at -60°C for 48 hours.

[0028] In the present invention, the deacetylation degree of the chitosan (CS) is 90%;

[0029] The polyethyleneimine (PEI) has a Mw of 600 g / mol, 99%;

[0030] The sodium alginate (SA) has a Mw of 198.11 g / mol;

[0031] The diatomaceous earth (DE) is analytically pure, and its content (in terms of SiO2) is ≥ 85.0%;

[0032] The polymer composite gel for heavy metal ion adsorption provided by the present invention is prepared by the above method. The prepared DE / CS-PEI@SA composite gel exhibits uniform wrinkles on its surface and has a thickness of 18.96 m 2 / g specific surface area and pore size of 1.5 to 80.0 nm, and showed good thermal stability both before and after adsorption.

[0033] The invention provides an application of a polymer composite gel for heavy metal ion adsorption, which is used for heavy metal ion adsorption, especially for the adsorption of heavy metal ions Pb(II) and Cu(II).

[0034] The design idea of ​​the present invention is as follows: Chitosan, polyethyleneimine and other polymer structures have abundant functional groups that can be used as adsorption sites. Therefore, by combining the advantages of functional group polymers and porous materials, organic porous materials are prepared to obtain adsorbents with high surface area, adjustable skeleton, good porosity and easy-to-operate mechanical structure. The present invention selects chitosan and polyethyleneimine with abundant adsorption sites, and forms a composite gel by polymer modification and cross-linking with diatomaceous earth and sodium alginate through ionic crosslinking. The porous composite gel adsorbent has the characteristics of rigid structure and large specific surface area, avoids the problem of agglomeration during use, is conducive to separation and recycling, and maximizes the operability and practicality of the porous bone adsorbent containing a multifunctional base.

[0035] In the present invention, SA is a biodegradable natural polysaccharide material, which contains abundant hydroxyl and carboxyl functional groups as controllable modification sites, the inorganic clay material DE has a layered porous structure, contains abundant active sites, and the surfaces of CS and PEI polymers have abundant amino and hydroxyl groups, which can serve as ion adsorption sites. At the same time, PEI serves as a nucleation site and an ion crosslinker to promote material modification and crosslinking to form a composite gel. As an ion adsorbent, the composite gel can be adsorbed by chemical chelation between functional groups and ions, and can also be physically adsorbed by a porous structure, thereby showing efficient ion adsorption performance. In addition, the preparation method of the present invention is simple, and the composite gel DE / CS-PEI@SA has a uniform morphology and good thermodynamic stability, and can be recycled and reused after adsorption.

[0036] Compared with the prior art, the composite gel DE / CS-PEI@SA provided by the present invention has a simple preparation method and simple product post-processing, and the composite gel has a large specific surface area, excellent thermodynamic stability, and high heavy metal ion adsorption efficiency, and can be recycled and reused after adsorption. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 The SEM images of DE, DE / CS and DE / CS-PEI@SA composite gels in Example 1; a1, a2, are DE; b1, b2 are DE / CS; c1, c2 are DE / CS-PEI@SA;

[0038] Figure 2 TG curves of DE, CS, PEI, SA and DE / CS-PEI@SA composite gel before and after adsorption in Example 1;

[0039] Figure 3 The adsorption performance of the composite gel DE / CS-PEI@SA with different compositions in Example 1 on Cu(Ⅱ) and Pb(Ⅱ), (a) and (c) different PEI dosages, (b) and (d) different DE and SA ratios.

[0040] Figure 4 (a) Dynamic and static adsorption performance curves of DE / CS-PEI@SA composite gel for Cu(Ⅱ) and Pb(Ⅱ) ions in Example 1; (b) Static secondary adsorption performance curves of DE / CS-PEI@SA composite gel for Cu(Ⅱ) and Pb(Ⅱ).

[0041] Figure 5 The EDS test spectrum of the DE / CS-PEI@SA composite gel after adsorption in Example 1; a and c are the adsorption of Cu(Ⅱ); b and d are the adsorption of Pb(Ⅱ);

[0042] Figure 6 SEM images of DE / MD-PEI@SA and DE / PEG-PEI@SA in Comparative Examples 1 and 2;

[0043] Figure 7 The adsorption curves are as follows: (a) is the adsorption curve of Cu(Ⅱ) by DE / MD-PEI@SA, DE / PEG-PEI@SA and DE / CS-PEI@SA; (b) is the adsorption curve of Pb(Ⅱ) by DE / MD-PEI@SA, DE / PEG-PEI@SA and DE / CS-PEI@SA. DETAILED DESCRIPTION

[0044] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0045] If no specific techniques or conditions are specified in the examples, they can be carried out according to the techniques or conditions described in the literature in the art or according to the product instructions.

[0046] PEI in the present invention was purchased from Shanghai Aladdin Chemical Reagent Co., Ltd., China, and DE, CS and SA were purchased from Sinopharm Chemical Reagent Co., Ltd. The deacetylation degree of chitosan (CS) was 90%; the Mw of the polyethyleneimine (PEI) was 600 g / mol, 99%; the Mw of the sodium alginate (SA) was 198.11 g / mol; the diatomaceous earth (DE) was analytically pure, with a content (in terms of SiO2) of ≥85.0%; polyethylene glycol PEG (Mw=44.05 g / mol), dextrin MD (analytical pure, Sinopharm); other chemical reagents were purchased from common reagent platforms and used directly unless otherwise specified.

[0047] Example 1

[0048] A method for preparing a polymer composite gel for heavy metal ion adsorption comprises the following steps:

[0049] 1) Weigh 5 g of diatomaceous earth DE and 2.65 g of sodium carbonate and dissolve them in 100 mL of deionized water, ultrasonically treat and stir for 30 min at room temperature, add saturated calcium chloride solution dropwise until precipitation is complete; finally filter the product CaCO3 / DE and wash it with deionized water for 3 times, and dry it in a 60°C oven for 10 hours; take 5 g of CaCO3 / DE and 1 g of chitosan CS and add them to 250 mL of Tris-HCl buffer solution (10 mmol, pH=8.5), stir at room temperature for 10 hours, filter and wash with deionized water until the washing filtrate becomes colorless, and dry it in a 60°C vacuum oven for 10 hours to obtain DE / CS.

[0050] 2) 1 g of sodium alginate was dissolved in 100 mL of deionized water at 60°C, and then 0.75 g of polyethyleneimine and 0.5 g of DE / CS were slowly added, and ultrasonic treatment was performed for 5 min to obtain a uniform mixed solution, and the mixture was kept at 60°C for 6 hours. The resulting mixed solution was then dropped into 100 mL of calcium chloride solution (3%, w / v) to form a composite gel, and the cross-linking reaction was performed at room temperature for 12 hours, and the mixture was soaked in 0.1 M hydrochloric acid for 2 hours, and then washed with 0.1 M sodium hydroxide solution and deionized water, respectively, and then freeze-dried at -60°C for 48 hours to obtain a DE / CS-PEI@SA composite gel.

[0051] The same method as in Example 1 was used to adjust different ratios of DE and SA and different amounts of PEI. The specific amounts of raw materials used are shown in Table 1.

[0052] Table 1 Composition of DE / CS-PEI@SA composite gel

[0053]

[0054]

[0055] The surface morphology of the composite gel was photographed by scanning transmission electron microscopy. Figure 1 A1 and a2 show that there are clear hollow and porous structures on the DE surface, which enhances the adsorption capacity of DE. Figure 1 b1 and b2 show the successful modification of DE by chitosan, with many spherical structures on its surface. Figure 1 Figures c1 and c2 show uniform wrinkles on the surface of the composite gel DE / CS-PEI@SA. The complex wrinkles observed in the material provide a larger surface area for the adsorbent.

[0056] The thermal stability of the raw materials and composite gel before and after adsorption was tested by TG thermogravimetric analyzer. Figure 2 As shown, the DE / CS-PEI@SA composite gel begins to decompose at about 50°C, which meets the operating temperature requirements of the adsorbent. The TG curve of the composite gel does not change much before and after adsorption, and it has good thermal stability as an adsorbent.

[0057] Figure 3 Adsorption performance of DE / CS-PEI@SA composite gels with different compositions for Cu(Ⅱ) and Pb(Ⅱ), (a) and (c) are different PEI dosages in DE / CS-PEI@SA (1:2) composite gels, (b) and (d) are different DE / CS:SA ratios (at 1:2, the PEI dosage is 0.75 g); the optimal component content of DE / CS-PEI@SA microspheres is 1 g sodium alginate, 0.5 g DE / CS and 0.75 g PEI, which has the best adsorption effect.

[0058] Example 2

[0059] An application of a polymer composite gel for heavy metal ion adsorption, which is used for heavy metal ion adsorption, and the specific method is:

[0060] Dissolve 1.255g CuSO4 and 0.7793g lead nitrate Pb(NO3)2 in deionized water to prepare 1000mg / L Cu(II) and Pb(II) standard stock solutions, respectively. Then, take 5mL of copper ion and lead ion standard stock solutions and transfer them to a 100mL volumetric flask to prepare 50mg / L Cu(II) and Pb(II) standard solutions. Add different volumes of standard solutions (0.00, 1.00, 2.00, 3.00, 4.00, 5.00, 6.00mL) to 7 50mL volumetric flasks containing 50mg / L solutions. When constructing the Cu(Ⅱ) standard curve, add 5mL EDTA-ammonium citrate solution and 5mL NH4Cl buffer solution in sequence, and measure the absorbance value at a wavelength of 450nm with 1mL starch solution and 5mL copper reagent. For the Pb(II) standard curve, after adding 1 mL of xylenol orange solution and 4 mL of hexamethylenetetramine solution, the absorbance was measured at a wavelength of 580 nm.

[0061] The adsorption effect of the composite gel on Cu(II) and Pb(II) ions can be expressed as the adsorption amount q e (mg / g) to evaluate, the adsorption amount q e The calculation formula is as follows:

[0062]

[0063] Where: C0, C eare the initial concentration of Cu(II) and Pb(II) solutions and the concentration when adsorption equilibrium is reached, mg / L;

[0064] m—mass of adsorbent, g;

[0065] V—volume of solution, mL.

[0066] In the initial adsorption experiment, 0.05 g of the composite gel particles prepared by the present invention were accurately weighed and introduced into a 50 mL stoppered colorimetric tube containing Cu(II) (200 mg / L, pH=6) and Pb(II) (300 mg / L, pH=4) solutions. The colorimetric tube was sealed and the static and dynamic adsorption processes were carried out in a fume hood and a shaker at ambient temperature. 1.00 mL of the solution was periodically poured into a 50 mL volumetric flask and diluted to volume with water for analysis. Subsequently, a buffer solution was introduced into the solution together with a color developer. The absorbance value of the Cu(II) ions was then measured at 450 nm and the absorbance value of the Pb(II) ions was measured at 580 nm until equilibrium was reached.

[0067] In Example 1, the adsorption of the composite gel prepared by combining 1g sodium alginate, 0.5g DE / CS and 0.75g PEI was carried out. The static and dynamic adsorption effects of Cu(II) and Pb(II) ions were tested as follows: Figure 4 As shown, the static adsorption capacity of the composite gel for Cu(Ⅱ) and Pb(Ⅱ) ions is stable at 125 and 250 mg / g, and can reach up to 170 and 260 mg / g, and the dynamic adsorption capacity is stable at 160 and 280 mg / g, and can reach up to 174.39 and 295.04 mg / g, indicating that the composite gel has a good adsorption effect. Figure 4 Figure b is the static secondary adsorption performance curve of DE / CS-PEI@SA composite gel for Cu(Ⅱ) and Pb(Ⅱ), with secondary adsorption retention rates of 82.5% and 77.49%, respectively, indicating good stability and reusability.

[0068] The changes in the element content of the composite gel before and after adsorption were tested by EDS, such as Figure 5 As shown in the figure, Cu(Ⅱ) and Pb(Ⅱ) ions were successfully adsorbed, mainly by chemical complexation with the amino, hydroxyl and carboxyl groups on the surface of the composite gel. In addition, the higher pore structure can also adsorb Cu(Ⅱ) and Pb(Ⅱ) ions through physical action.

[0069] Comparative Example 1

[0070] A method for preparing DE / MD-PEI@SA (diatomaceous earth / dextrin-polyethyleneimine@sodium alginate), specifically comprising the following steps:

[0071] 1) Weigh 5 g DE and 2.65 g sodium carbonate and dissolve them in 100 mL deionized water. Ultrasonic treatment and stirring at room temperature for 30 min, add saturated calcium chloride solution dropwise until precipitation is complete, filter the product CaCO3 / DE and wash it with deionized water for 3 times, and dry it in a 60°C oven for 10 hours; take 5 g CaCO3 / DE and 1 g dextrin MD (analytical grade, Chinese medicine) and add them to 250 mL Tris-HCl buffer solution (10 mmol, pH = 8.5), stir at room temperature for 10 hours, filter and wash with deionized water until the washing filtrate becomes colorless, and dry it in a 60°C vacuum oven for 10 hours to obtain DE / MD.

[0072] 2) 1 g of sodium alginate was dissolved in 100 mL of deionized water at 60 ° C, and then 0.75 g of polyethyleneimine and 0.5 g of DE / MD were slowly added, and ultrasonic treatment was performed for 5 min to obtain a uniform mixed solution, and the reaction was maintained at 60 ° C for 6 hours. The mixed solution was then dropped into 100 mL of calcium chloride solution (3%, w / v) to form a composite gel, cross-linked for 12 hours, treated with 0.1 M hydrochloric acid for 2 hours, washed with 0.1 M sodium hydroxide solution and deionized water, respectively, and then freeze-dried at -60 ° C for 48 hours to obtain a DE / MD-PEI@SA composite gel.

[0073] Comparative Example 2

[0074] A method for preparing DE / PEG-PEI@SA (diatomaceous earth / polyethylene glycol-polyethyleneimine@sodium alginate), specifically comprising the following steps:

[0075] 1) Weigh 5g DE and 2.65g sodium carbonate and dissolve them in 100mL deionized water, ultrasonically treat and stir for 30min at room temperature, and add saturated calcium chloride solution dropwise until precipitation is complete. Finally, filter the product CaCO3 / DE, wash it with deionized water 3 times, and dry it in a 60℃ oven for 10 hours. Take 5g CaCO3 / DE and 1g polyethylene glycol PEG (Mw=44.05g / mol) and add them to Tris-HCl buffer solution (250mL, 10mmoL, pH=8.5), stir at room temperature for 10 hours, filter and wash with deionized water until the washing filtrate becomes colorless, and dry it in a 60℃ vacuum oven for 10 hours to obtain DE / PEG.

[0076] 2) 1 g of sodium alginate was dissolved in 100 mL of deionized water at 60°C, and then 0.75 g of polyethyleneimine and 0.5 g of DE / PEG were slowly added, and ultrasonic treatment was performed for 5 min to obtain a uniform mixed solution, and the reaction was maintained at 60°C for 6 hours. The mixed solution was then dropped into 100 mL of calcium chloride solution (3%, w / v) to form a composite gel, cross-linked for 12 hours, treated with 0.1 M hydrochloric acid for 2 hours, washed with 0.1 M sodium hydroxide solution and deionized water, respectively, and then freeze-dried at -60°C for 48 hours to obtain a DE / PEG-PEI@SA composite gel.

[0077] Figure 6 Ac in the figure is the SEM image of DE / MD-PEI@SA. Figure 6 df in the figure is the SEM image of DE / PEG-PEI@SA. Figure 1 By comparison, it can be seen that Figure 1 The gel prepared in the experiment has uniform wrinkles on its surface, which can provide a larger surface area for the adsorbent. Figure 6 The two materials prepared in the experiment have wrinkles relative to Figure 1 The most important comparison is still through the comparison of adsorption effects. As shown in Table 2, the adsorption effects of the embodiment materials of the present invention on copper and lead are much higher than those of the materials in the two comparative examples.

[0078] According to the same method as in Example 2, the composite gels prepared by Comparative Examples 1 and 2 were used as adsorbents for the dynamic adsorption of Cu(II) and Pb(II), and the adsorption effect of the composite gels was compared with that of Example 1. The results are as follows: Figure 7 And as shown in Table 2.

[0079] Table 2 Adsorption data of three composite gels for Cu(Ⅱ) and Pb(Ⅱ)

[0080]

[0081] The adsorption amount of Cu(II) and Pb(II) by the composite gels prepared in Comparative Examples 1 and 2 is significantly lower than that of the DE / CS-PEI@SA gel in Example 1.

[0082] The present invention selects diatomite (DE), chitosan (CS), polyethyleneimine (PEI) and sodium alginate (SA) as raw materials, and promotes polymer modification and cross-linking to form a composite gel through an ion cross-linking method. In the present invention, firstly, the prepared DE and CS are added to a buffer solution, and fully stirred at room temperature to promote the precipitation of chitosan-modified diatomite (DE / CS); then the dried DE / CS is added to a sodium alginate solution, PEI is used as a nucleation site and an ion cross-linking agent, and then the mixed solution is added dropwise to a calcium chloride solution to form a composite gel; finally, a hydrochloric acid solution is used for soaking treatment to form a porous structure of the composite gel, and a composite DE / CS-PEI@SA gel is obtained after washing with a sodium hydroxide solution and water and freeze drying.

[0083] The present invention prepares a composite gel material by an ion crosslinking method. SA, as a biodegradable natural polysaccharide material, contains abundant hydroxyl and carboxyl functional groups as controllable modification sites. DE, as an inorganic clay material, has a layered porous structure and contains abundant active sites. The surfaces of CS and PEI polymers have abundant amino and hydroxyl groups, which can serve as ion adsorption sites. At the same time, PEI serves as a nucleation site and an ion crosslinking agent to promote material modification and crosslinking to form a composite gel. As an ion adsorbent, the composite gel can be adsorbed by chemical chelation between functional groups and ions, or by physical adsorption through a porous structure, thereby exhibiting efficient ion adsorption performance. In addition, the preparation method of the present invention is simple, and the composite gel DE / CS-PEI@SA has a uniform morphology and good thermodynamic stability, and can be recycled and reused after adsorption. The composite gel prepared in the present invention has a large specific surface area and many adsorption groups, and exhibits good adsorption performance for heavy metal ions Pb (II) and Cu (II), with the maximum adsorption amounts reaching 295.04 and 174.39 mg / g, respectively. The secondary adsorption amounts for Pb (II) and Cu (II) are 222.97 mg / g and 125.84 mg / g, respectively, and the secondary adsorption retention rates are 82.5% and 77.49%, respectively. The composite gel has good stability and reusability, and has good application value in removing heavy metal ions in sewage.

[0084] The description of the above embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A method for preparing a polymer composite gel for heavy metal ion adsorption, characterized in that: The preparation method comprises the following steps: 1) After ultrasonically dispersing diatomite DE and sodium carbonate in water, a saturated calcium chloride solution is added until precipitation is complete to obtain CaCO3 / DE; CaCO3 / DE is mixed with chitosan CS in a buffer solution, and stirred for reaction to obtain chitosan-modified diatomite DE / CS; 2) Chitosan-modified diatomaceous earth DE / CS and polyethyleneimine PEI are added to a sodium alginate SA aqueous solution, and after ultrasonic dispersion, the mixture is heated for reaction. The obtained mixed solution is then dropped into a calcium chloride solution. After the cross-linking reaction, the mixture is soaked in hydrochloric acid, washed, and freeze-dried to obtain a DE / CS-PEI@SA composite gel.

2. The preparation method according to claim 1, characterized in that: In step 1), CaCO3 / DE and chitosan are mixed in a buffer solution, wherein the mass concentration of chitosan is 0.4%; the mass concentration of CaCO3 / DE is 2%.

3. The preparation method according to claim 1 or 2, characterized in that: In step 1), the stirring reaction refers to stirring the reaction at room temperature for 10 hours.

4. The preparation method according to claim 1, characterized in that: In step 2), the mass ratio of chitosan-modified diatomaceous earth DE / CS to sodium alginate in the sodium alginate aqueous solution is 1:0.5-3.

5. The preparation method according to claim 1 or 4, characterized in that: In step 2), the mass ratio of chitosan-modified diatomaceous earth DE / CS to polyethyleneimine PEI is 1:0.5-2.

6. The preparation method according to claim 1, characterized in that: In step 2), the heating reaction refers to reacting at 60° C. for 6 hours.

7. The preparation method according to claim 1, characterized in that: In step 2), the cross-linking reaction is carried out for 12 hours.

8. The preparation method according to claim 1, characterized in that: In step 2), the freeze drying refers to freeze drying at -60°C for 48 hours.

9. A polymer composite gel for heavy metal ion adsorption prepared by the preparation method according to any one of claims 1 to 8.

10. An application of the polymer composite gel for heavy metal ion adsorption according to claim 9, characterized in that: Used for heavy metal ion adsorption.

Citation Information

Patent Citations

  • Preparation method of enhanced chitosan-based aerogel for adsorbing heavy metal ions

    CN111482163A

Cited By

  • Method for preventing and controlling filamentous algae pollution of water body based on biology

    CN120398272A

  • Sewage medicament containing aluminum-silicon porous material as well as preparation method and application of sewage medicament

    CN121198230A